2022
DOI: 10.1016/j.ygyno.2021.10.081
|View full text |Cite|
|
Sign up to set email alerts
|

Incidence, treatment, and survival trends in older versus younger women with epithelial ovarian cancer from 2005 to 2018: A nationwide Danish study

Abstract: decreased among women <70 years of age but was stable for women ≥70 years during 2005-2018.• The proportion of patients with advanced EOC not undergoing debulking surgery increased from 2005 to 2018.• During the same period, the proportion of patients having 0 cm residual disease after debulking surgery increased.• During the same period, cancer-specific survival increased for both younger and older EOC patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…Consistent with previous findings, one out of two older women with advanced-stage EOC did not undergo PDS or IDS [3]. Patients with NDS had higher age and worse PS at diagnosis than those undergoing debulking surgery.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Consistent with previous findings, one out of two older women with advanced-stage EOC did not undergo PDS or IDS [3]. Patients with NDS had higher age and worse PS at diagnosis than those undergoing debulking surgery.…”
Section: Discussionsupporting
confidence: 89%
“…Epithelial ovarian cancer (EOC) is the most lethal gynecological malignancy for which long-term survival is conditioned by surgery often combined with chemotherapy [1,2]. The balance between performing this comprehensive treatment combination and the EOC patient population, with a considerable number of older women, poses a continuous challenge in a clinical setting [3]. Older patients with EOC repeatedly demonstrate poor survival compared to younger [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A larger tumor burden was associated with a greater tumor burden, which we believe is closely related to the FIGO stage of the disease; thus, future studies could subdivide stages IA and IB. Previous studies have suggested that age is a high-risk factor for a prognosis for EOC, and some studies have suggested that age ≥ 70 years is associated with a 1.4-fold increased risk of CSS [15]. Our results showed that those who were < 50 years old had a worse prognosis, which may be related to the trend of younger onset of OCCC and the faster disease progression in younger patients compared with older patients.…”
Section: Discussionmentioning
confidence: 44%
“…However, the lack of data specific to older patients, seldom included or highly selected in pivotal trials, 5 8 and the fear of excessive toxicity, 9 may explain these inequalities. Furthermore, treatment strategies for older patients are based on subgroup analyses of pivotal randomized trials, 10 , 11 prospective real-life unselected population-based studies, 12 14 retrospective studies, 15 and specific clinical trials conducted in older patients, 16 , 17 but these seldom integrate assessment of geriatric covariates. In this context, it appears useful to describe the available evidence on cancer characteristics at diagnosis in older patients, the general impact of age on outcomes, and all successive treatment steps.…”
Section: Introductionmentioning
confidence: 99%